STRATEGI PENGEMBANGAN AGROINDUSTRI SARI COCO DI KOTA PEKANBARU - Evy Maharani; Rani Astuti; Susy Edwina; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2023)
One of the agro-industrial activities carried out in Pekanbaru is the nata de coco agro-industry. Nata de coco is made from coconut water waste which can be a form of fresh drink that resembles jelly or jelly. This study aims to determine the strengths, weaknesses, opportunities and threats of Sari Coco agro-industry and formulate a development strategy for Sari Coco agro-industry in Pekanbaru City. This research was conducted in Sari Coco agro-industry in Rumbai Sub-district, Pekanbaru City. Descriptive analysis was conducted to analyse the strengths, weaknesses, opportunities and threats of Sari Coco agro-industry. To formulate the development strategy of Sari Coco agro-industry in Pekanbaru City, SWOT analysis (strengths, weaknesses, opportunities, threats) and AHP (Analytic Hierarchy Process) were used. The strengths of Sari Coco agro-industry are MUI Halal certified, having regular customers, cheaper product prices and being able to compete with similar production, as well as diverse flavours and shapes. The priority strategies for the development of Sari Coco agro-industry in Pekanbaru City are maintaining competitive product prices, utilising technology to attract customers, improving product marketing, utilising technological advances, innovating packaging sizes and taking advantage of market opportunities.